Penerapan Metode SAW (Simple Additive Weighting) pada Perankingan SMA-SMA di Kabupaten Minahasa Selatan - Sagrang, Handra R; Paendong, Marline S; Rindengan, Altien J (d'CARTESIAN:Jurnal Matematika dan Aplikasi, 2020)
Education is one of the most important factors for the life of every human being to gain wider insights to support a better life. This study uses variables regarding the national standard of high school education, namely Content Standards, Educator and Education Staff Standards, Graduates Competency Standards, and Educational Assessment Standards in South Minahasa District which are applied using the SAW (Simple Additive Weighting) method by building An Expert System Application. The results obtained are based on calculations done by researchers and application calculations have the same value that is 97,569 namely SMA 1 Amurang.